2003
DOI: 10.1073/pnas.2235925100
|View full text |Cite
|
Sign up to set email alerts
|

Functional deactivations: Change with age and dementia of the Alzheimer type

Abstract: Young adults typically deactivate specific brain regions during active task performance. Deactivated regions overlap with those that show reduced resting metabolic activity in aging and dementia, raising the possibility of a relation. Here, the magnitude and dynamic temporal properties of these typically deactivated regions were explored in aging by using functional MRI in 82 participants. Young adults (n ‫؍‬ 32), older adults without dementia (n ‫؍‬ 27), and older adults with early-stage dementia of the Alzhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

88
514
9
11

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 673 publications
(622 citation statements)
references
References 51 publications
(95 reference statements)
88
514
9
11
Order By: Relevance
“…Such a difference was not observed during the second stage when COV and ALZV animals showed a similarity in maze performance. This is consistent with some previous retrospective [24,25] and prospective longitudinal [23,26] studies that support the hypothesis that in- creased use of cognitive skills and higher levels of education can protect against the development of AD. However, epidemiological studies cannot determine which activities or the combination of them are more important [27] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such a difference was not observed during the second stage when COV and ALZV animals showed a similarity in maze performance. This is consistent with some previous retrospective [24,25] and prospective longitudinal [23,26] studies that support the hypothesis that in- creased use of cognitive skills and higher levels of education can protect against the development of AD. However, epidemiological studies cannot determine which activities or the combination of them are more important [27] .…”
Section: Discussionsupporting
confidence: 92%
“…AD is associated with loss of cognition and mild impairment in memory [23] . The present study evaluated the effect of extract prepared from Lavandula angustifolia on spatial maze performance.…”
Section: Discussionmentioning
confidence: 99%
“…This shift was interpreted as a compensatory response to dysfunction in the MTL. The DN also has been studied in older adults with MCI, who show weaker functional connectivity in this network compared to healty elderly, consistent with studies showing that AD patients have less deactivation of and weaker functional connectivity in the DN 109,180 . These effects of MCI have been found in the PCC 181 , and in its connections to other regions 182 .…”
Section: Risk Factors For Alzheimer's Disease: Mild Cognitive Impairmentsupporting
confidence: 75%
“…In young adults, DN regions maintain strong functional interconnections during tasks requiring self-reference or theory of mind 101,102 , and also during the resting state 103,104 . Several studies have found that the reduction of DN activity during externally-driven cognitive tasks is less pronounced in old adults, relative to young adults 58,[105][106][107][108][109][110][111][112] . Functional connectivity of the DN also is reduced with age during working memory tasks 113 and during periods of rest 105,[114][115][116] .…”
Section: Box 1 Measuring Activity In Brain Networkmentioning
confidence: 99%
“…The most common method of analyzing data from a standard FMRI activation experiment is to create a model of the expected BOLD response [using an a-priori model of the haemodynamic response function (HRF)] and estimate the magnitude of the response using methods of parameter fitting within the framework of the generalized linear model (GLM). Such methods have successfully been used to detect regionally altered brain activation in AD and MCI [see for example Dickerson et al, 2004;Golby et al, 2005;Lustig et al, 2003;Rombouts et al, 2005b], and brain activation changes after pharmacologic treatment in dementia [Goekoop et al, 2004;Rombouts et al, 2002;Saykin et al, 2004]. Modelbased analysis approaches, however, rely heavily on assumptions about the temporal characteristics of haemodynamic signals and are limited to cases where these underlying assumptions well characterize the effects of interest.…”
Section: Introductionmentioning
confidence: 99%